Kartun Politik dalam Harian Merdeka di Indonesia pada Masa Revolusi Kemerdekaan (1945-1947) - Nada Nur Rofa; Aam Abdillah; Widiati Isana (Historia Madania: Jurnal Ilmu Sejarah, 2018)
Political cartoons published by Merdeka Daily newspaper during the Independence Revolution of the Republic of Indonesia took part in following socio-political dynamics that were taking place at the time. This study aims to see how the Merdeka Daily was during the Independence Revolution in 1945-197, and how the political cartoons published by Harian Merdeka during the Independence Revolution in 1945-197. The method used in this study is the historical research method, which includes heuristic, criticsm, interpretation, and historiography stages. The results of this study indicate that during the period 1945-1947, Merdeka Daily took part in the struggle to defend the independence of the Republic of Indonesia, among others by providing information related to current events and situations, presenting public service announcements to support independence, and presenting political cartoons that expressed his views on the events and situations that were happening at that time. The political cartoons published by Merdeka Daily in 1945-1947 can at least be grouped into four major themes, there are (1) exposing the cruelty of the enemy, (2) stirring up the spirit of resistance, (3) taunting the NICA-Netherland, and (4) Indonesia, Netherland, and International World. Keyword: Political Cartoons, Merdeka Daily, Independence Revolution.